2017
DOI: 10.1007/s00520-017-3602-2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pancreatic insufficiency using pancreatic extract in patients with advanced pancreatic cancer: a pilot study (PICNIC)

Abstract: Despite intriguing survival results, this study was not sufficiently feasible to proceed to a fully powered comparative study. A multi-centre study would be required to exclude a significant difference in outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 28 publications
1
19
1
Order By: Relevance
“…A more recent randomized study showed an increase in overall survival in patients randomized to taking PERT but did not reach statistical significance due to a low enrollment rate, with only 18 patients randomized prior to closure of the study. 23 A prospective cohort study of unresectable PC patients receiving chemotherapy showed improved changes in body mass index and increased overall survival of patients who received PERT retrospectively compared with prior patients receiving chemotherapy as historical controls. 24 These clinical trials investigating PERT used various doses, ranging from 40,000 to 72,000 units of lipase for meals and 20,000 to 36,000 units of lipase per snack.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent randomized study showed an increase in overall survival in patients randomized to taking PERT but did not reach statistical significance due to a low enrollment rate, with only 18 patients randomized prior to closure of the study. 23 A prospective cohort study of unresectable PC patients receiving chemotherapy showed improved changes in body mass index and increased overall survival of patients who received PERT retrospectively compared with prior patients receiving chemotherapy as historical controls. 24 These clinical trials investigating PERT used various doses, ranging from 40,000 to 72,000 units of lipase for meals and 20,000 to 36,000 units of lipase per snack.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies reported sufficient data to calculate the pooled prevalence of PEI 11,[23][24][25][26][27]30 and seven the effects of PERT. 13,14,[26][27][28][29][30] The patient's characteristics included in the studies are shown in Table 1. Six hundred and seventy-three APC patients were included, with data on PEI available in 513 patients.…”
Section: Characteristics Of Included Patientsmentioning
confidence: 99%
“…11,13,24,26 PEI was defined by FE-1 <200 lg/g in four studies, 11,24,30 by N-benzoyl-L-tyrosyl-P-aminobenzoic acid (NBT-PABA) test in two studies, 26,27 by triolein breath test and/or oleic acid breath test and or CFA <93% in one study, 23 by CFA<85% and/or FE-1<200 lg/g and/or faecal fat excretion >20 g/d in one study 25 and by clinical suspicion and/or weight loss >10% in two studies. 14,28 Data about PERT use were reported in all 11 studies: eight studies also reported the length of followup 11,13,24,[26][27][28][29][30] and six presented data about health status. 13,25,[27][28][29][30] A summary of the results of all the performed quantitative syntheses (meta-analyses) is shown in Table 3.…”
Section: Pooled Prevalence Of Pancreatic Exocrine Insufficiency In Apcmentioning
confidence: 99%
“…In a retrospective, nonrandomized study of 66 unresectable PC patients receiving PERT with nutritional counseling and palliative care or standard palliative care without PERT, median survival of patients receiving PERT was longer than that of those with standard palliative care (301 days vs. 89 days) . More recently, a randomized study showed an increase in OS in patients randomized to taking enzymes but did not reach statistical significance because of a low enrollment rate . Additionally, a prospective study of unresectable patient receiving chemotherapy showed improved changes in BMI and increased OS of patients who received PERT compared with historical controls .…”
Section: Intervention For Pawlmentioning
confidence: 99%